Characterisation of the human thyroid peroxidase gene mutations (S) in patients with congenital dyshormonogenetic hypothyroidism / Lee Ching Chin - Lee, Ching Chin (2013)
Congenital hypothyroidism (CH) is a public health concern affecting 1 / 3000 - 4000 newborn babies. In reference to this, thyroid peroxidase (TPO) abnormality, typically inherited as autosomal recessive traits was found to be one of the causes of dyshormonogenetic CH. Our group had previously identified a homozygous c.1159G>A mutation in exon 8 of the TPO gene of CHP41. In this study, the TPO gene of CHP41’s family members was screened for the c.1159G>A mutation and the results showed that all family members carried the same mutation either in homozygous or heterozygous forms. In addition, another 20 unrelated cases of dyshormonogenetic CH were also included in this study. DNA sequence analysis of the TPO gene in these 20 unrelated patients revealed the presence of five TPO mutations: three were novel (c.670_672del in exon 7, c.1186C>T in exon 8 and c.1502T>G in exon 9) while another two had been previously reported (c.2268dup in exon 13 and c.2647C>T in exon 16). Moreover, 12 polymorphisms including two that are novel (c.1-192C>A in a GC box and c.180-6C>A at 6 bp upstream of exon 4), were also found in the 21 unrelated patients. This study shows that only individuals associated with either homozygous or compound heterozygous form of TPO mutation were affected with dyshormonogenetic CH whereas family members of patients with one mutant allele remained asymptomatic. In silico functional analyses indicated that all of the six mutations affected normal activity of TPO protein. Furthermore, the novel c.180-6C>A polymorphism is predicted to reduce the intrinsic strength of the natural splice site of exon 4 which could lead to an activation of other potential splice sites. Meanwhile, it is also believed that the novel c.1-192C>A polymorphism in the GC box might alter the expression levels of TPO gene in an individual. Further investigation on patients with c.2268dup mutation through biochemical and gene expression analyses confirmed the devastating effects of the mutation. A novel TPO mRNA transcript which was believed to be associated with nonsense-associated altered splicing (NAS) mechanism was detected in patients associated with the c.2268dup mutation. In addition, lower expression of TPO protein was also detected in thyroid tissues with lesions compared to those of normal areas in the same patients with c.2268dup. In conclusion, mutations in the TPO gene are an underlying genetic cause of CH with dyshormonogenesis in the current cohort of patients.